Efektivitas Integrasi Model Student Teams Achievement Division (STAD) dengan Multimedia dalam Meningkatkan Keterampilan Kolaborasi Siswa Sekolah Dasar - Basuki, Sigit Rahmat; Hidayah, Ratna (Paedagogie, 2026)
Collaboration skills are one of the essential 21st-century skills that students must master to face future challenges. In reality, low levels of collaboration skills and fundamental issues related to the collaborative abilities of fifth-grade students are still found in learning. This study aims to analyze the effectiveness of integrating the Student Teams Achievement Division (STAD) model with multimedia in improving the collaboration skills of fifth-grade students at SD Negeri Karangtanjung. This research employed a collaborative Classroom Action Research (CAR) approach. The findings indicate that the integration of the STAD model with multimedia can enhance the collaboration skills of fifth-grade students at SD Negeri Karangtanjung, with a percentage of 73.47% in cycle I (categorized as fairly good), 84.37% in cycle II (categorized as good), and 92.18% in cycle III (categorized as very good). It can be concluded that integrating the Student Teams Achievement Division (STAD) model with multimedia is proven effective in improving the collaboration skills of fifth-grade students at SD Negeri Karangtanjung.